Complete mitochondrial genome of Pelecanus crispus and its phylogeny - Huang, Tian (Mitochondrial DNA B Resour, 2019)
The Dalmatian Pelican (Pelecanus crispus), in the order Pelecaniformes, its habitat is distributed in Europe, Asia, and Africa. It is a large waterfowl that is of international concern. In this study, we first sequenced and described the complete mitochondrial genome and phylogeny of P. crispus. The results showed that the whole genome of P. crispus was 16,131 bp in length, and contained 13 protein-coding genes, 22 transfer RNA genes, two ribosome RNA genes, and one non-coding control region. The overall base composition of the mitochondrial DNA was 30.48% for A, 23.15% for T, 31.68% for C, and 14.69% for G, with a GC content of 46.37%. A phylogenetic tree of P. crispus in Pelecaniformes confirmed that P. crispus was sister to C. occidentalis. This information will be useful in the current understanding of the phylogeny and evolution of Pelecaniformes.